“TECHNOLOGY, ENTERTAINMENT, DESIGN (TED)” TALK IN TEACHING VOCABULARY - Feny Rahmawati; Iskhak Said; Misbahudin Misbahudin (Universitas Galuh, 2020)
This study deals with the investigation of an analysis of teaching vocabulary by using technology, entertainment, design (TED) Talk. The previous study conducted in university students, while the present study is a case study in one of senior high school in Cilacap. This study was aimed at investigating teachers’ way and knowing students’ perception in teaching vocabulary by using TED Talk. In conducting this study the writers used qualitative research in which case study was employed to collect the data from participants in this research, that were English teacher who taught vocabulary using TED Talk and ten grade students of senior high school students’ perception. Moreover, classroom observation, questionnaire, and interview were the instruments used by the writers in collecting the data. It could be concluded that most of the students are very interested in learning, it was very significant in relation to their learning interest, it was very helpful in mastering new vocabulary, it was strongly agree that it was given positive results for their learning achievement.Keywords: TED Talk, Vocabulary